2016
DOI: 10.1111/1346-8138.13510
|View full text |Cite
|
Sign up to set email alerts
|

Partial unilateral lentiginosis is mosaic neurofibromatosis type 1 or not?

Abstract: Partial unilateral lentiginosis (PUL) is a rare pigmentation disorder characterized by numerous lentigines with sharp margins in the midline in one or more dermatomes. Its segmental pattern suggests that this presentation accompanied by café-au-lait spots, Lisch nodule or neurofibromas has a close relationship with mosaic neurofibromatosis type 1 or segmental neurofibromatosis (NF) in particular. In a group of 16 patients with PUL, who presented at the dermatology outpatient clinic between 1998 and 2015, an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Partial unilateral lentiginosis is a skin pigmentation disorder in the form of asymptomatic lentigines 7 that appear as brownish macules 8 scattered on normal skin 2 , 3 in a segmental pattern with the involvement of one or more dermatomes 3 , 6 with well-defined midlines. 2 Park et al 9 reported that the onset of PUL occurs at a mean age of 14 years (range = 6–26 years) and is mainly diagnosed between 7–41 years, with a mean age of 27 years. The prevalence is similar in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Partial unilateral lentiginosis is a skin pigmentation disorder in the form of asymptomatic lentigines 7 that appear as brownish macules 8 scattered on normal skin 2 , 3 in a segmental pattern with the involvement of one or more dermatomes 3 , 6 with well-defined midlines. 2 Park et al 9 reported that the onset of PUL occurs at a mean age of 14 years (range = 6–26 years) and is mainly diagnosed between 7–41 years, with a mean age of 27 years. The prevalence is similar in males and females.…”
Section: Discussionmentioning
confidence: 99%